1996
DOI: 10.1164/ajrccm.153.5.8630593
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hypertonic saline, amiloride, and cough on mucociliary clearance in patients with cystic fibrosis.

Abstract: In patients with cystic fibrosis (CF), dehydration of airway secretions leads to a decrease in mucociliary clearance (MCC). We examined the acute effect of MCC of a single administration by aerosolization of hypertonic saline (7%) (HS), amiloride (0.3% in 0.12% NaCl) (AML) and a combination of AML and HS (AML + HS) in 12 patients with CF using a radioaerosol technique. Isotonic saline [0.9%] (IS) was used as a control solution. As both the AML and HS solutions induced cough in some patients, the last nine pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
134
2
6

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 202 publications
(148 citation statements)
references
References 23 publications
6
134
2
6
Order By: Relevance
“…Exacerbations were defined by the need for intravenous antibiotics or using a symptom score involving increased sputum production, lethargy, dyspnea, and fever. In previous smaller studies of CF subjects, a single nebulized dose of 6 -7% HS increased mucociliary clearance at 60 and 90 min, as measured by radionucleotide imaging (3,5). Increased mucociliary clearance was dose-dependent up to 12% HS in 10 adults treated with a single dose and tested at 90 min (4).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Exacerbations were defined by the need for intravenous antibiotics or using a symptom score involving increased sputum production, lethargy, dyspnea, and fever. In previous smaller studies of CF subjects, a single nebulized dose of 6 -7% HS increased mucociliary clearance at 60 and 90 min, as measured by radionucleotide imaging (3,5). Increased mucociliary clearance was dose-dependent up to 12% HS in 10 adults treated with a single dose and tested at 90 min (4).…”
Section: Discussionmentioning
confidence: 80%
“…Prior clinical studies also support the efficacy of various inhaled hyperosmolar agents in CF (3)(4)(5)(6). The recent study by Donaldson et al (1) concludes that hypertonic saline produces sustained elevation in airway surface liquid (ASL) volume, which improves mucociliary clearance in the airways.…”
Section: Cystic Fibrosis (Cf)mentioning
confidence: 98%
“…HS has a favorable effect on mucus rheology in vitro through hydration of the airway surface [40]. Another postulated effect of HS is that by increasing salt concentrations on the luminal side of the respiratory epithelium the viscous mucus will hydrate, improving mucociliary clearance [41,[56][57][58][59][60][61]. The landmark trial by Elkins et al (evidence level 1B) demonstrated that 48-weeks treatment with 7% HS nebulized twice daily improved the absolute difference in pulmonary function between groups, but not the decline in pulmonary function over time.…”
Section: Hypertonic Salinementioning
confidence: 99%
“…Nebulized HS can induce acute airway narrowing or bronchospasm and cough (Supplementary Tables 2), [11,[55][56][57][58][59][60][61][62][63][64][65][66][67][68][69] but in most cases these symptoms decrease after a few weeks so that the majority of patients find HS tolerable [55,62,63,68]. Rodwell et al were the first to describe acute airway responsiveness to inhaled 10% saline in a group of CF subjects with asthma-like symptoms [11].…”
Section: Hypertonic Salinementioning
confidence: 99%
See 1 more Smart Citation